ANALISIS SOAL PENILAIAN AKHIR SEMESTER MUATAN PEMBELAJARAN IPA BERBASIS HOTS KELAS V SD MUHAMMADIYAH PURWODADI - Nur Riya Asti; Nur Ngazizah; Arum Ratnaningsih (LPPM Universitas Cipta Mandiri, 2024)
21st century learning requires having high-level thinking skills starting from elementary school in accordance with the government program managed by the Ministry of Education and Culture which aims to improve the quality of learning and graduates. This research aims to find out the results of the analysis of final semester assessment questions for HOTS-based science learning content for class V Muhammadiyah Purwodadi Elementary School. The research method used is a qualitative method, with descriptive data analysis techniques, a type of document analysis. Based on the results of the analysis, there are 2 categories of thinking skills in the final semester assessment question papers for class V science at SD Muhammadiyah Purwodadi. This category is LOTS or low level thinking skills, there are 10 questions for multiple choice, 7 questions for filling in, and 3 questions for description. Meanwhile, for the HOTS category or high level thinking skills, there are 6 questions for multiple choice, 3 questions for filling in, and 1 question for description. All the results of this analysis were taken from 30 science lesson content questions from theme 1 to theme 5.